2006
DOI: 10.1364/ao.45.007294
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance sensors based on uniform-waist tapered fibers in a reflective configuration

Abstract: We present a configuration for surface plasmon resonance sensors based on uniform-waist tapered optical fibers and reflective elements. Once the fiber is tapered fulfilling the adiabatic criterion, a multilayer including a metallic medium is asymmetrically deposited on the uniform waist of the fiber. This feature provides the resonant excitation of multiple surface plasma waves. In addition, a mirror is produced at the fiber tip by a chemical Tollens reaction. In this way, the sensor operates in a reflective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…The introduction of a second dielectric layer has proven to be decisive to control the location of the plasmon resonance, which is very important when moving this resonance outside the usual ranges of refractive indices or wavelengths [23,24]. We depict the fabrication process, characterize the transducers, and compare its performance in terms of polarization dependence with other devices.…”
Section: Spr and Polarizationmentioning
confidence: 99%
“…The introduction of a second dielectric layer has proven to be decisive to control the location of the plasmon resonance, which is very important when moving this resonance outside the usual ranges of refractive indices or wavelengths [23,24]. We depict the fabrication process, characterize the transducers, and compare its performance in terms of polarization dependence with other devices.…”
Section: Spr and Polarizationmentioning
confidence: 99%
“…In this case the coupling happens between the light propagating through the long taper and a surface plasmon [85]. Different materials have been coated along the taper surface to form surface plasmon sensors for temperature, refractive index and bio-sensing measurements [86][87][88][89][90]. Low-loss solgel-derived silica films were also successfully deposited on the uniform waist of a tapered fiber [91], which has the ability to dope with rare earths and other materials, leading to a new class of all-fiber devices for sensing applications.…”
Section: Adiabatic Long Tapermentioning
confidence: 99%
“…If we take into account that we have shown that a reflective element can be added at the fiber end and that we can develop then a "dip-probe" configuration, where the sensing element has been reduced to very few centimeters and can be remotely interrogated, it is apparent that SPR sensors based in these elements can be very well suited to in situ, realtime measurements. [5] …”
Section: Dl-uwts: What and Whymentioning
confidence: 99%